TRAINING OF PROFESSIONALS WITH POSITIVE HUMAN QUALITIES IN THE LESSONS OF FINE AND APPLIED ARTS IN THE EDUCATION OF THE MODERN SPIRIT - Abdimuminova Dildora (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Today, a number of documents of the government of the republic are aimed at the development of our country in accordance with the requirements of comprehensive standards. In particular, great importance is attached in the education of young people to the use of culture, values, national art, the wonderful works of art created by our ancestors and famous all over the world.